Ovarian cancer stage, variation in transvaginal ultrasound examination rates and the impact of an urgent referral pathway: A national ecological cohort study. (14th August 2019) - Ladegaard Baun, Marie‐Louise; Falborg, Alina Z.; Hjertholm, Peter; Petersen, Lone K.; Vedsted, Peter
Abstract: Introduction: The aim of this study was to determine whether variation in transvaginal ultrasound examination rates in Danish general practice populations is associated with ovarian cancer outcomes, and to explore the impact of the introduction of a cancer patient pathway for ovarian cancer. Material and methods: We performed a national register‐based cohort study of gynecological cancer‐free women aged 40 years or above, living in Denmark and listed with a specific general practitioner in 2004‐2014. Practice populations were divided into quartiles according to the general practitioners' transvaginal ultrasound propensity in the preceding year. Associations between transvaginal ultrasound rates and ovarian cancer outcomes were analyzed using Poisson and logistic regression. Results: We included 2769 general practices with 1 739 422 listed women, of whom 5325 were diagnosed with ovarian cancer during the study period. Practices varied twofold in transvaginal ultrasound rates before and after the implementation of the cancer patient pathway. Before the cancer patient pathway was introduced, women listed with practices with the highest transvaginal ultrasound rates were diagnosed with earlier stages of ovarian cancer (odds ratio 1.38, 95% confidence interval 1.06 to 1.81) and had a higher proportion of borderline tumors (incidence rate ratio 1.38, 95% confidence interval 1.10 to 1.75) compared with women least exposed to transvaginal ultrasound. After the cancer patient pathway, no significant differences were identified between the groups. Conclusions: Before the cancer patient pathway, women exposed most to transvaginal ultrasound were significantly more likely to be diagnosed with early stage ovarian cancer compared with those least exposed to transvaginal ultrasound. After the cancer patient pathway was implemented, the difference disappeared. This suggests that increased awareness and access to transvaginal ultrasound is useful for diagnosing early‐stage ovarian cancer.